2011
DOI: 10.1292/jvms.11-0098
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Two Novel Cytochrome P450 3A131 and 3A132 in Liver and Small Intestine of Domestic Cats

Abstract: ABSTRACT. Cytochrome P450 3A (CYP3A) is the major subfamily of CYP, one of the most important metabolizing enzymes for drugs in humans and other mammals. We found two novel CYP3A genes, CYP3A131 and CYP3A132 in domestic cats (Felis catus). Both feline CYP3A proteins consist of 504 deduced amino acids and show high identity with canine CYP3A homologues and those of some artiodactyls. CYP3A131 transcripts were expressed predominantly in liver and small intestine, and to a negligible extent in other tissues, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The CYP3A family consists of CYP3A131 and 3A132 , with previous reports of CYP3A131 mRNA transcript expression in small intestine and liver, and limited CYP3A132 expression only in liver(Honda et al, 2011). RNA-Seq results indicate CYP3A131 expression was present in all five experimentally acquired tissues examined, with the majority of expression in liver and duodenum.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The CYP3A family consists of CYP3A131 and 3A132 , with previous reports of CYP3A131 mRNA transcript expression in small intestine and liver, and limited CYP3A132 expression only in liver(Honda et al, 2011). RNA-Seq results indicate CYP3A131 expression was present in all five experimentally acquired tissues examined, with the majority of expression in liver and duodenum.…”
Section: Discussionmentioning
confidence: 69%
“…Reported differences between canine and feline, include feline CYP2B6 expression in lung and duodenum but not in the liver(Okamatsu et al, 2017) and duplication of CYP2E (Tanaka et al, 2005). Additional feline CYP previously described include CYP2A13 (Okamatsu et al, 2015), 3A131 , 3A132 (Honda et al, 2011), and 2D6 (Komatsu et al, 2010). While probe substrates suggest differences between the various species, the limited information regarding CYP expression in the feline limits the ability to predict drug efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mRNA expressions of all CYP isoforms were not statistically different between control and exposure groups, CYP3A12 (1.8-to 1.9-fold) and CYP3A131 (2.0-fold) tended to be higher in the exposure group compared with those in the control group. We recently reported that CYP3A is dominant subfamily in the liver [16] and it could play a major role in hepatic xenobiotic metabolism for cats [15,16]. However, the liver microsome in cats revealed lower CYP3A activity than in humans and dogs and the relationship between molecular structure and metabolic activity is still largely unknown in cats [39].…”
mentioning
confidence: 99%
“…However, little is known about the CYPs that are involved in the biotransformation of xenobiotics in cats despite their remarkable species differences in drug metabolism. CYP3A131 is one of the major CYP isoforms, following CYP2E2, CYP2A13 and CYP2E1 in the feline liver, while CYP3A131 transcript was predominant in the small intestine [3, 5]. Metabolic activities of CYP3A131 and the interactions with 17 compounds have been determined using 7-benzyloxy-4-(trifluoromethyl)-coumarin (BFC), a fluorogenic substrate [5].…”
mentioning
confidence: 99%